UPAYA GURU PPKN DALAM MENGEMBANGKAN KECERDASAN MORAL PESERTA DIDIK DI SMP NEGERI 33 HALMAHERA SELATAN - Rustam Hasyim; Askar Udin (EDUKASI, 2021)
The background of this research is to develop students 'moral intelligence and learning models as well as the lack of PPKn teachers themselves who always develop and educate students' morale in teaching and learning activities in class, besides that students have not been accustomed to answering questions that have the ability to think. they. The objectives of this study are (1) To determine the efforts of the teacher in the development of moral intelligence of students in schools at 33 Halmahera Selatan Public Middle School. (2) To find out the factors that influence the development of moral intelligence of students in schools at 33 Halmahera Selatan State Junior High School. The subjects of this study were the Principals, Teachers and Students of SMP Negeri 33 Halmahera Selatan. Data collection techniques used observation, interviews, and documentation study. The results of this study: the efforts of the teacher in developing the moral intelligence of students are important to note because it is a method used to find out how the moral intelligence of students is when interacting in the school, family, and community environment in the teaching and learning process in the classroom. able to understand the material being taught and be able to apply it in everyday life. As a form of effort in developing students' moral intelligence, it can be seen from the attitude of piety, discipline, obedience, responsibility, and honesty of students. Basically, the awareness of students is needed, because awareness of the importance of moral intelligence will bring students to good things. If students are aware of the importance of moral values, students will be aware of the laws they get if they violate school rules, students as students can certainly distinguish between good or bad things, and actions that are allowed or prohibited. The availability of facilities and infrastructure is also a factor in developing students' moral intelligence.